Physically based rainfall: Runoff modelling in the northern Ethiopian highlands: The case of Mizewa watershed - Taffese, T. (Bahir Dar University, 2011)
A study was conducted in Fogera catchment by selecting a smaller watershed of an area 27 km2. A detailed review of existing rainwater management practices including mapping of locations were performed by surveying using high resolution hand – held Geographic Positioning System (GPS). Some selected practices were proposed corresponding to different landscape of the watershed by consulting what the farmers (and other local stakeholders) think needed and might be needed in the future. The flow was measured at the outlet of the watershed using staff gauge and flow meter to test the efficiency of the model. The hydro-meteorological data were collected from the nearby stations and the quality of those data was checked. The detail land use data was also prepared by surveying and the soil map were used as per FAO classification. Missed hydro-meteorological records were filled depending on their percentage missing; using arithmetic mean for those stations having less than 10 % data missing and neighboring stations for other stations. Weather generator was also created to fill-in missing gaps and generates climate data. Soil and Water Assessment Tool (SWAT 2005) integrated with Arc GIS and Map Window were used to model the watershed which account spatial and temporal variation of inputs at HRUs level. The results were compared and sensitivity analysis has been carried out for SWAT – CN method and resulted in ESCO and CN as the most sensitive parameter. The output were calibrated for the year 1995-2004 using flow data obtained by area proportion from Gumara for Mizewa watershed and Gumara flow for Gumara watershed ( to derive parameters for Mizewa watershed) reasonable result were obtained (0.67 Ens, 0.684 R2). The model was also validated for the year 2005-2009 (0.657 Ens, 0.755 R2) in both of the cases and compared with the observed value. The study benefits the society by letting to know the available water resource and how to improve and manage the resource.